2017 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2017
DOI: 10.1109/iros.2017.8206258
|View full text |Cite
|
Sign up to set email alerts
|

Safe robotic grasping: Minimum impact-force grasp selection

Abstract: Abstract-This paper addresses the problem of selecting from a choice of possible grasps, so that impact forces will be minimised if a collision occurs while the robot is moving the grasped object along a post-grasp trajectory. Such considerations are important for safety in human-robot interaction, where even a certified "human-safe" (e.g. compliant) arm may become hazardous once it grasps and begins moving an object, which may have significant mass, sharp edges or other dangers. Additionally, minimising colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Fn m shown in Figure 2 is the normal force (Fn) value plus Sm (safety margin) applied by each finger when lifting event occurs. Fn m can be expressed as in equation (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fn m shown in Figure 2 is the normal force (Fn) value plus Sm (safety margin) applied by each finger when lifting event occurs. Fn m can be expressed as in equation (2).…”
Section: Methodsmentioning
confidence: 99%
“…For a robotic hand, grasping and manipulation is a complex task containing a movement plan in terms of kinematic and force control in both statics and dynamics. 2 The reason why this task is complex is due to the problems associated with the geometry, durability, hardness, and surface properties of the object to be gripped. The analytical modeling problems related to these issues are classified by Cutkosky 1 as follows: Geometry Kinematic Dynamic Constitutive relations.…”
Section: Introductionmentioning
confidence: 99%
“…The selection criterion is based on the object's inertial parameters. Image from [86]. (b) Again, the robot uses the inertial parameters to select a grasp that will minimise the required joint torque to execute a task.…”
Section: Exploitation Of Inertial Parametersmentioning
confidence: 99%
“…This equation, anong with Eqs. (4) and (3) give the velocity of the object as a function of the pusher velocity:…”
Section: A Quasi-static Robot Pushing Mechanicsmentioning
confidence: 99%
“…Apart from visual info, recent research has shown that the inertial properties of an object, namely mass, centre of mass (CoM) and inertia tensor (which encodes the mass distribution), can make the grasping and manipulation process more efficient. Examples include minimum-disturbance grasp synthesis [1], as well as safe and minimum-effort manipulation planning [2] [3]. As a result, it is highly beneficial for an autonomous robot to be able to estimate the handled object's inertial parameters prior to grasping it, as this can lead to more efficient manipulation.…”
Section: Introductionmentioning
confidence: 99%